2005
DOI: 10.1002/ppap.200400092
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric Pressure Deposition of Micropatterned Nitrogen‐Rich Plasma‐Polymer Films for Tissue Engineering

Abstract: Summary: A novel atmospheric‐pressure plasma‐polymerised thin film material has been deposited on various substrates using a pilot scale dielectric barrier discharge (DBD) reactor. Deposition kinetics and physico‐chemical characterisation data of nitrogen‐rich plasma‐polymerised ethylene (PPE:N) films, obtained using feed gas mixtures of N2 (ca. 10 slm) and C2H4 (ca. 10 sccm) are described. Nitrogen concentrations, [N], in the PPE:N films up to ca. 40% were determined by XPS; the concentrations of N‐functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
182
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(194 citation statements)
references
References 13 publications
10
182
1
1
Order By: Relevance
“…A TMOSPHERIC pressure glow discharges (APGD) have recently attracted much attention, largely because they offer a chamberless route to many scientific disciplines, including analytical chemistry [1], nanoscience [2], biology and medicine [3]- [5], space exploration [6], and display technologies [7]. Interest in APGD is also motivated by their scope for new low-temperature plasma physics in a highly collisional regime [8].…”
Section: Introductionmentioning
confidence: 99%
“…A TMOSPHERIC pressure glow discharges (APGD) have recently attracted much attention, largely because they offer a chamberless route to many scientific disciplines, including analytical chemistry [1], nanoscience [2], biology and medicine [3]- [5], space exploration [6], and display technologies [7]. Interest in APGD is also motivated by their scope for new low-temperature plasma physics in a highly collisional regime [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known, for example, that nitrogen-rich organic coatings promote cell adhesion and differentiation of mesenchymal stem cells; Marasescu et al [23] have focused their investigations on plasma-deposited N-rich films obtained from C 2 H 4 /NH 3 or C 2 H 4 /N 2 gas mixtures in LP (L-PPE:N) and AP DBD (H-PPE:N) systems, respectively. AP deposited PPE:N coatings were used by Girard et al [26] to produce surfaces with alternated micrometric cell-adhesive and cellrepulsive domains. Square PPE:N arrays were obtained through a micrometric polyimide mask.…”
Section: Atmospheric Pressure Cold Plasmas For Materials Processingmentioning
confidence: 99%
“…Girard-Lauriault et al [98] fabricated a N-rich surface using a plasma discharge of N 2 and ethylene on a variety of polymeric substrates, while a polyimide mask was used to deposit the patterns. Chondrocyte and U937 macrophage seeding revealed that a minimum of 25% nitrogen incorporation was required to have a good cell adhesion.…”
Section: Other Surface Chemistriesmentioning
confidence: 99%